2014
DOI: 10.1039/c3nr05231a
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanorods/ZnS·(1,6-hexanediamine)0.5 hybrid nanoplates hierarchical heteroarchitecture with improved electrochemical catalytic properties for hydrazine

Abstract: Novel hierarchical heteronanostructures of ZnO nanorods/ZnS·(HDA)0.5 (HDA = 1,6-hexanediamine) hybrid nanoplates on a zinc substrate are successfully synthesized on a large scale by combining hydrothermal growth (for ZnO nanorods) and liquid chemical conversion (for ZnS·(HDA)0.5 nanoplates) techniques. The formation of ZnS·(HDA)0.5 hybrid nanoplates branches takes advantage of the preferential binding of 1,6-hexanediamine on specific facets of ZnS, which makes the thickening rate much lower than the lateral gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…30 For the inset curve, all diffraction peaks can be indexed to the typical orthorhombic phase ZnS(en) 0.5 hybrid material with good crystallization, agreeing well with literature reports of ZnS(en) 0.5 . 9,11,31 In addition, a diffraction peaks at 10.24 is observed, which is a characteristic peak of inorganic-organic hybrid composites with intercalated layer structures, 10,12 indicating ethylenediamine molecules successfully insert into the interlayer of ZnS under current experimental conditions. The products of ZnS(en) 0.5 hybrid would be affected either changing the reaction temperature or reaction time, as shown in Fig.…”
Section: Characterizationsmentioning
confidence: 93%
See 2 more Smart Citations
“…30 For the inset curve, all diffraction peaks can be indexed to the typical orthorhombic phase ZnS(en) 0.5 hybrid material with good crystallization, agreeing well with literature reports of ZnS(en) 0.5 . 9,11,31 In addition, a diffraction peaks at 10.24 is observed, which is a characteristic peak of inorganic-organic hybrid composites with intercalated layer structures, 10,12 indicating ethylenediamine molecules successfully insert into the interlayer of ZnS under current experimental conditions. The products of ZnS(en) 0.5 hybrid would be affected either changing the reaction temperature or reaction time, as shown in Fig.…”
Section: Characterizationsmentioning
confidence: 93%
“…For hybrid ZnS(en) 0.5 , the two sharp absorption peaks located at 3240 and 3110 cm À1 are the typical N-H stretching vibration, and the absorption peaks at about 2980 and 2970 cm À1 belong to the C-H vibration. 12 However, the small absorption peak, particularly at 1620 cm À1 , is assigned to the stretching vibrations of the N-H connect to Zn 2+ in a ve-membered ring. In addition, the three absorption peaks at 1600, 1360, and 1070 cm À1 are attributable to -NH 2 , -CH 2 and -CN stretching, respectively.…”
Section: Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The incorporation of a small amount of O, having electronegativity much larger than that of S, Se, or Te can dramatically influence the electronic band structure, such as band gap bowing and hence the absorption and photoluminescence (PL) emission characteristics can be tuned over the entire UV-visible range, by tuning the oxygen content in the samples. 8,9 Though a lot of experimental and theoretical studies have been carried out on Mg x Zn 1Àx O, Cd x Zn 1Àx O, and Be x Zn 1Àx O semiconductors but relatively less attention has been paid on ZnS 1Àx O x due to the large difference in the electronegativity between O and S resulting in a larger bowing parameter. 10 However, recently it has been shown that the use of the ZnOS buffer layer can effectively enhance the conversion efficiency of Cu(In, Ga)Se 2 -based thin film solar cells and can also be used to improve ZnO device performance.…”
mentioning
confidence: 99%
“…18,22,[29][30][31][32] In the ZnO/ZnS heterojunction, the advantageous properties of both semiconductor nanomaterials are combined. 18,22,[29][30][31][32] In the ZnO/ZnS heterojunction, the advantageous properties of both semiconductor nanomaterials are combined.…”
Section: Introductionmentioning
confidence: 99%